In vitro characterization of UB Forest (Malang, Indonesia) indigenous bacteria as plant growth promoting bacteria (PGPB) - LUQMAN QURATA AINI; IRISA TRIANTI; SHOLIKAH WIDYANITTA RACHMAWATI; ANTON MEILUS PUTRA; NABILLA ALYA ANASTASYA; ADI SETIAWAN (Society for Indonesian Biodiversity, 2023)
Abstract. Aini LQ, Trianti I, Rachmawati SW, Putra AM, Anastasya NA, Setiawan A. 2023. In vitro characterization of UB Forest (Malang, Indonesia) indigenous bacteria as plant growth promoting bacteria (PGPB). Biodiversitas 24: 4558-4565. UB Forest, an educational forest of Universitas Brawijaya in Malang, East Java, has a mega-biodiversity of microbial germplasm. Previously, we obtained several UB Forest indigenous bacterial isolates and tested them on various plant commodities. However, the comprehensive characterization of the bacteria to produce IAA hormone, to overcome biotic and abiotic stresses as well as their potency as biofertilizers in vitro has not been carried out yet. In this study, we conducted in vitro assays to elucidate the potency of UB Forest indigenous bacterial isolates as Plant Growth Promoting Bacteria (PGPB). The molecular identification showed that the bacterial strains were dominated by the Pseudomonads, namely Pseudomonas versuta UB-36, P. aeruginosa UB-52, P. lundensis UB-53, P. migulae UB-54, and P. koreensis UB-62. Other strains were Enterococcus gallinarum UB-55 and Lysinibacillus fusiformis UB-64. Of the 7 bacterial strains, only 3 could inhibit Xanthomonas campestris. All bacterial strains were able to produce IAA, whereas five bacteria can solubilize phosphate, six bacteria can fix nitrogen, and four bacteria have both activities. All bacterial strains can grow at pH 5-6, salinity 5-15%, temperature 60°C, and 15% polyethylene glycol (PEG) drought stress media. The results suggested that the UB Forest indigenous bacterial strains have a role as plant growth-promoting bacteria (PGPB) and are expected to support the growth of plants grown under biotic and abiotic stress conditions.